The Parliamentary Debate – A Critical Look at the Practice (2009-2019) - Kiselova, Nataliуa (Media and Language, 2020)
The parliamentary government is a form of governance of a state, a political regime and a „big public debate stage“. The article presents the activities of the National Assembly during the period 2009-2019 as a political regime and a debate stage. It represents a critical analysis of the constitutional and political functions of the Bulgarian Parliament. Negative trends in parliamentary procedures are presented through the implementation of legislative, constitutive and control functions. There is a refusal or avoidance of parliamentary debate between the parliamentary majority and the parliamentary opposition.
Keywords: National Assembly; parliamentary debate; anti-parliamentary practices